Use of Online Information in Musculoskeletal Conditions: An Analysis of Google Trends Data. Issue 3 (14th April 2022) - Fritsch, Carolina G.; Duong, Vicky; Chen, Lingxiao; Hunter, David J.; McLachlan, Andrew J.; Ferreira, Paulo H.; Ferreira, Manuela L.
Abstract : Supplemental digital content is available in the text. Abstract : Background/Objective: We aimed to investigate the yearly online public interest for gout, low back pain, neck pain, osteoarthritis, and rheumatoid arthritis, the most popular topics searched for these conditions, and the association between the change in their interest over time and the sociodemographic index of the search location. Methods: We conducted online searches in Google Trends for the aforementioned conditions between 2004 and 2020. The search volumes for each condition (relative to all searches conducted in the period) and the top and rising related queries and topics were downloaded and summarized. Results: There was a rise in the online interest for musculoskeletal conditions between 2008 and 2020, with low back pain (annual percent change, 7.4; 95% confidence interval [CI], 7.1–7.7) and neck pain (annual percent change, 7.2; 95% CI, 6.9–7.5) presenting the highest increases. There was a negative, statistically significant, but small association between change in online interest and the country's sociodemographic index for low back pain (−0.007; 95% CI, −0.011 to−0.003), neck pain (−0.005; 95% CI, 0.009 to −0.001), and rheumatoid arthritis (−0.009; 95% CI, −0.017 to −0.001) between 2013 and 2020. The interest for the cause and symptoms of the selected conditions increased over time, except for gout. The proportion of queries and topics related to treatment of all conditions decreased over time. Conclusions: The worldwide interest in musculoskeletal conditions increased between 2008 and 2020. The public seems more interested in understanding what musculoskeletal conditions are and less interested in which treatment options are available. The results can guide the development of educational campaigns for musculoskeletal conditions.